Sosialisasi Potensi BADAN USAHA MILIK DESA (BUMDes) Makmur Untuk Meningkatkan Pemberdayaan Perekonomian Desa Bojong Gede - Santi Octavia; Novita Wahyu Setyawati; Susilo Utomo (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2022)
The establishment of Village BUM is intended as an effort to accommodate all activities in the economic sector and/or public services managed by the Village and/or inter-Village cooperation. Villages can establish Village-Owned Enterprises called Village BUM which are managed with the spirit of family and cooperation. Businesses that can be run by Village BUM are businesses in the economic sector or public services in accordance with the provisions of laws and regulations. The establishment of Village BUM was agreed upon through village deliberations and stipulated by village regulations. This Empowerment activity aims to increase the potential of Bumdes Makmur which is located in Bojong Gede Village - Bogor Regency, West Java. Based on a preliminary survey of conditions in Bojong Gede Village, low information about the existence of Bumdes was identified. The public in general does not know much, even though the condition of the majority of people working as farmers, traders and craftsmen certainly needs a village institution that is able to accommodate the potential of the community and the natural potential of the village in order to become a new source of income for the community. Empowerment activities provided in the form of socialization and discussion.